If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11 + -4x = 0.5 Solving 11 + -4x = 0.5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + -4x = 0.5 + -11 Combine like terms: 11 + -11 = 0 0 + -4x = 0.5 + -11 -4x = 0.5 + -11 Combine like terms: 0.5 + -11 = -10.5 -4x = -10.5 Divide each side by '-4'. x = 2.625 Simplifying x = 2.625
| 19+-5p=-1 | | (3/5)w-(1/7)=(-3/7)w+(3/7) | | 7r=-7 | | 12-(1/26)(2x)=6-(1/26)(x) | | 7x*8k=8x-17k | | 5x+2/7x-6 | | 4y^2-5y^2+7y^2= | | [SQRT(x+3)]=2[SQRT(x)] | | x^3+2x^2-6x=12 | | (5/4)y-(3/8)=(7/2)y+(3/8) | | 0.1=.07+x(0.12) | | 2(x/3-3)=16 | | 3(3n-3)=-54 | | (9x-3)*(-0.7)= | | 6+9z=7 | | -6v+11=-4v+1 | | (-5i)+(I)= | | 2x^2+58=20x | | (-7)(8)-(-6)(-2)= | | 6x^2+2x-17=0 | | 1.5z=z | | 8x+10+2x=90 | | (1/x)+(1/x+3)=(1/4) | | -9z-9=-4z+6 | | 8+-25=-57 | | -6x-5=31 | | 18=2g+4 | | -8w-12=-2w+18 | | y/5-7=2 | | I-3=-7 | | x/(x+1)+(x+1)/x=3 | | 1=t/3-1 |